2019
DOI: 10.1142/s1793604719500255
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultrathin g-C3N4/graphene nanocomposites with excellent visible-light photocatalytic performances

Abstract: Graphitic carbon nitride (g-C3N[Formula: see text] has drawn increasing interest as an efficient photocatalyst. To further improve its photocatalytic activity, herein we coupled g-C3N4 with graphene to construct ultrathin g-C3N4/graphene (g-C3N4/G) nanocomposites by a pyrolysis-sonication-hydrothermal method. Under the illumination of visible-light, g-C3N4/G nanocomposites with 10[Formula: see text]wt.%G can degrade 92% Rhodamine B (RhB) in 120[Formula: see text]min, which is higher than that (57%) from pure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Melamine was used as a precursor for synthesis of pure g-C3N4. Typically, melamine was put in a muffle furnace powder at 550 0 C for 4h [12,15]. Then, obtained products were collected and washed with deionized water several times for further use.…”
Section: Synthesis Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melamine was used as a precursor for synthesis of pure g-C3N4. Typically, melamine was put in a muffle furnace powder at 550 0 C for 4h [12,15]. Then, obtained products were collected and washed with deionized water several times for further use.…”
Section: Synthesis Of Compositesmentioning
confidence: 99%
“…Graphic carbon (g-C3N4) has attracted great attention for many applications because of their unique physicochemical property and stable allotrope. With the structure of a two-dimensional framework, g-C3N4 exhibits basic surface sites, electron-rich sites and highly stable hidrothermal and chemical stability [12]. The properties play an important role in catalytic application.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 is a diagram of the methods currently used to prepare g-C3N4. The most commonly used methods are thermal polymerization, vapor deposition, high temperature, and high-pressure synthesis and solvothermal synthesis [56][57][58]. Thermal polymerization is the preparation of g-C3N4 by pyrolysis of nitrogen-rich organic matter and polycondensation of precursor itself.…”
Section: Synthesis Of Graphitic Carbon Nitride Nanomaterialsmentioning
confidence: 99%
“…Figure 3 is a diagram of the methods currently used to prepare g-C 3 N 4 . The most commonly used methods are thermal polymerization, vapor deposition, high temperature, and high-pressure synthesis and solvothermal synthesis [56][57][58].…”
Section: Synthesis Of Graphitic Carbon Nitride Nanomaterialsmentioning
confidence: 99%
“…The authors reported a 14.9% improvement in tensile strength of PLA pellets on coating pellets with polydopamine. Wang et al [ 47 ] reported a 71.1% increase in compressive strength of calcium silicate structures on coating them with polydopamine. This significant increase in compressive strength was attributed to the absorption ability of polydopamine that hindered propagation of cracks.…”
Section: Introductionmentioning
confidence: 99%